What is poetry? : the essential guide to reading & writing poems - Rosen, Michael, 1946- (Candlewick Press, 2019)
Poet and critic Michael Rosen uses classic poems by English poetry masters to define poetry, describe what poetry can do, and to explain how to read, write, and appreciate poetry.